절패모(浙貝母)의 항염 및 진해거담 효과에 대한 실험연구 - 김진후; 양원경; 이수원; 유이란; 김승형; 박양춘; Kim, Jin Hoo; Yang, Won Kyung; Lee, Su Won; Lyu, Yee Ran; Kim, Seung Hyung; Park, Yang Chun (대한한방내과학회지, 2020)
Objective: This study aimed to evaluate anti-inflammatory and antitussive expectoration effects of Friltillariae Thunbergii Bulbus (FTB) in a mouse model. Materials and Methods: To evaluate the anti-inflammatory effects of the FTB, we conducted in vitro experiments using RAW264.7 cells. An MTT assay and enzyme-linked immunosorbent assay (ELISA) were carried out to examine the anti-inflammatory effects of FTB. The expectorant effect on phenol red secretion, the antitussive effect on cough induced by ammonia solution, and leukocyte increased inhibition effects in acute airway inflammation in the animal model were confirmed. Results: FTB did not show cytotoxicity in the experimental group at 10, 30, 50, 100, 300, or 500 ㎍/ml and significantly inhibited the increase of NO, TNF-α and IL-6 in the experimental groups at 30, 50, 100, 300, and 500 ㎍/ml concentrations. In sputum, cough, and acute airway inflammation animal models, FTB significantly increased phenol red secretion in the 400 mg/kg administration group. FTB significantly reduced the number of coughs and significantly increased cough delay time in both 200 and 400 mg/kg dose groups. FTB decreased the white blood cell count in BALF (bronchoalveolar lavage fluid) in the 400 mg/kg administration group. Conclusion: Our study revealed that FTB elicits antitussive and expectorant effects by inhibiting inflammatory cytokines, increasing sputum secretion, suppressing cough, and reducing inflammatory cells. We concluded that FTB is a highly promising agent for respiratory tract infection with therapeutic opportunities.